Hubungan Tingkat Pengetahuan tentang PHBS dengan Perilaku Membuang Sampah pada Tempatnya di Siswa SMP Negeri 9 Seunuddon, Aceh Utara - Erna Safitri; Sela Safitria; Wada Islami; Ade Rahma Azizah; Intan Safitri; Maulidar Maulidar; Mulia Utari (Pusat Riset dan Inovasi Nasional, 2025)
The aim of this research was to determine the relationship between the level of knowledge and the behavior of throwing away waste among students at MTS, N Seunuddon, North Aceh. The sample in this study was 18 grade 3 students with a quantitative research design with a cross sectional design. Instrument testing included Independent Variables which included Level of Knowledge and dependent variables including waste disposal behavior at MTS.N 9 Seunuddon North Aceh and statistical tests The type of sampling used in this research is total sampling. The research results showed that almost half of the respondents knew the results of calculating the respondent's knowledge before conducting counseling. Most of them had good knowledge with the number of respondents being 10 respondents (55.6%), and 8 respondents (44.4%) getting less good results out of a total of 18 respondents (100,%). It is known that the results of calculating the knowledge of respondents after being provided with educational counseling said that the level of knowledge was very good with the number of respondents being 17 (94.4%) and 1 respondent (5.6%) being less than good out of a total of 18 respondents. With the results of this research, it is hoped that school administrators, especially teachers, will provide health education or counseling about Clean and Healthy Living Behavior (PHBS), especially about knowledge and behavior of disposing of waste to their students.